Penerapan Media Loose Parts dalam Meningkatkan Motorik Halus dan Kreativitas Anak Usia 4-5 Tahun di TK Islam Terpadu Geranio Medan - Vivi Chairani; Nurmawati Nurmawati; Inom Nasution (Institut Nalanda, 2024)
The research aims to determine the increase in loose parts media in the Geranio Medan Integrated Islamic Kindergarten. which is based on the learning outcomes of students in the application of loose parts media in the Kindergarten A2 group at the Geranio Integrated Islamic Kindergarten with a total of 12 students consisting of 5 girls and 7 boys. The type of research used in this research is classroom action research (PTK) with qualitative and quantitative data sources. Data analysis carried out by the researcher was the results of each cycle, the researcher made a comparison of the percentage of children's scores before the action and after the action using loose parts media which was carried out to improve children's fine motor skills and creativity. Based on the results of research conducted by researchers using cycle I and cycle II actions, it can be concluded that the use of loose parts media to improve children's fine motor skills can improve with very good improvements exceeding the 80% completion limit, namely 89.84%. Before any action takes place, children's fine motor skills and creativity have begun to develop, but in cycle I they have begun to develop. The increase from cycle I to the 1st meeting was 31.51%, cycle I to the 2nd meeting the children began to be enthusiastic about making bicycles from tree branches 58.59%, cycle II to the 1st meeting the children were able to make hand movements when decorating their activities by making bracelets from colorful pipettes 75%, in cycle II of the 2nd meeting the children were able to complete their activities creatively by making raindrops using various kinds of loose parts media and 89.84% of the children began to be able to follow the activities modeled by the teacher.